One Step Equations
X+5=13
X=8
SIMPLIFY: 5(x+6)
5x+30
3k+10=22
K=12
2x-1/4=2/4
X=3/8
6(x-5)=18
X=6
2x=20
X=10
SIMPLIFY: -1/2(6x-12)
-3x+6
4y−7=21
y=7
⅓X+8=15
5(2x-4)=-14
X=6/10 OR 3/5
X-(-5)=30
X=25
SIMPLIFY: -9(x – 4) – 6x?
-15x+36
w/-4+18=26
w=-32
4.5x + 16 = 11.5
X=-1
1/2(x+4)=-12
X=-28
X/12=17
X=204
SIMPLIFY: 4r + 10(2r) − 8r?
16r
b/25 - 83=-86
b=-75
-4.5x + 27 = 45
X=-4
2/3(3x-6)=8
X=6
-7x=56
X=-8
SIMPLIFY: 24r − 3(2r − 5t) − 4t?
18r+11t
2= x/3 - 19
x=63
7.5x-9.15=47.1
X=7.5
-2(1.7x+1.2)-3.8=4
X=-3